Synthesis and electrochemical capacitance performance of polyaniline doped with lignosulfonate. Issue 93 (11th October 2015) - Xu, Hailing; Jiang, Huang; Li, Xingwei; Wang, Gengchao
<x xml:space="preserve">Abstract</x> Polyaniline doped with lignosulfonate (PANI/LGS) was prepared by using a facile oxidative polymerization of aniline with (NH4)2S2O8 as an oxidant, and its electrochemical capacitance performance was investigated.